Harvesting hope for climate action and food systems in a grave new world - Schuttenbelt, Daan; Thorton, Philip; Dinesh, Dhanush; Loboguerrero, Ana Maria; Martinez-Baron, Deissy (SAGE Publications, 2025)
Multilateralism, as epitomized by Western liberal hegemony and the concomitant intergovernmental agreements and institutions set up after World War II, is in crisis. Reductions in development funding coupled with inadequate climate action and limited progress toward the Sustainable Development Goals do not bode well for the challenges that food systems are increasingly facing. In crisis lies opportunity, however. Here, the outputs of a process lasting several months are described, involving stakeholders and experts from organizations ranging from funders, NGOs, government, the private sector, and research institutes, whose objective was to consider what is needed to facilitate the move toward more sustainable and equitable food systems. Along with a scan of recent writings on alternative narrative framings of food systems as drivers of behavioral change, one output of this process was the identification of five potential elements of a modified global architecture for accelerating climate action in food systems. These five were embracing multiplicity, expanding localism, addressing justice, being positive and inclusive in messaging, and out-competing legacy systems. These are neither new nor original ideas, but if actioned together their implications could be far-reaching for those working at the intersection of agricultural development and climate. Some planned, concrete actions for each element are briefly described—the early stages of an organizational experiment to gauge their effectiveness in contributing to food system reconfiguration at different scales.